Dynamics of thermal Marangoni stagnation point flow in dusty Casson nanofluid. (3rd September 2022) - Gowda, R. J. Punith; Mallikarjuna, Hogarehally Basavarajappa; Prasannakumara, B. C.; Kumar, R. Naveen; Manjunatha, P. T.
ABSTRACT: The current perusal presents a stagnation point (SP) flow and heat transfer analysis of Casson dusty nanofluid over a surface with Marangoni convection. Here, non-Newtonian nanoliquid suspended with T i 6 A l 4 V as nanoparticle and dust particles in base fluid sodium alginate is utilized to scrutinize the present two-phase boundary layer model. Further, suitable transformations are used to reduce the modelled governing equations to a set of ordinary differential equations. Later, numerical solutions are secured using an efficient and well-known Runge-Kutta-Fehlberg fourth fifth-order (RKF-45) method using the shooting technique. The impacts of the governing parameters on various profiles are illustrated with the help of graphs. The significant findings of the current model are that the escalating values of the Marangoni number deteriorations the velocity gradient of both dusty nanoliquids. The augmentation of dust particle mass concentration declines the thermal gradient of both liquid and particle phases. The boost up values of dust particle mass concentration and thermal dust parameter advances the rate of heat transfer.